Interaction of N-succinyl diaminopimelate desuccinylase with orphenadrine and disulfiram - Diaz Sanchez, Angel Gabriel (2020)
The emergence of multiresistant, often persistent, pathogenic bacteria emphasizes the need for a continuous identification of new pharmacological targets of enzymatic nature, and the development of selective inhibitors against them. Ubiquitously present in most bacteria, the enzyme metallohydrolase N-succinyl diaminopimelate desuccinylase (DapE) is required for the biosynthesis of meso-diaminopimelate (mDAP) and lysine, both essential components of bacterial peptidoglycan. DapE activity has been recognized as critical for bacterial growth; and thus, it is a potential pharmacological target. In order to develop effective inhibitors against DapE, understanding of structural and functional features of the enzyme must be used in the design, such as the interaction of its metal centers with ligands, as well as its effect on global protein conformational changes that seem to produce an induced fit after ligand binding. Here, we propose the potential application of currently approved drugs, used in different medical fields, orphenadrine and disulfiram, as possible inhibitory compounds against DapE, based on studies of equilibrium ligand binding, inhibition, thermal stability and molecular docking into Enterococcus faecium and Escherichia coli DapE enzyme homologs. Drugs were selected based on key structural features, including the presence of soft heteroatoms or π-bonds that are known to interact with DapE active site. Enzymes from selected bacteria were chosen based on the pattern of infection, persistence, and drug resistance as well to study an enzyme from the two Gram classification. Furthermore, the information presented here can further provide structural details about key interacting functional groups, which should be considered in the design and development of a new generation of antibiotics that can target the essential DapE enzyme.